Solitary superficial acral angiomyxoma: An infrequently reported soft tissue tumor - Mahendra M Kura; Saurabh R Jindal (Wolters Kluwer Medknow Publications, 2014)
Superficial angiomyxomas (SA) are clinically variable, infrequent, benign skin lesions. They are usually located on the trunk, but can also appear on the lower limbs, head, and neck. The present case, hence, is unusual, because the lesion developed on the toe. They are diagnosed histologically, and are characterized by being poorly delimited tumors with the presence of interstitial myxoid material and scanty cellularity. We discuss the clinical and histological features of digital SA as well as a brief outline of other myxoid lesions.